Twin Deficits in Developing Economies - Furceri, Davide (IMF Working Papers; Working Paper ;, 2018)
This paper provides new evidence on the existence and magnitude of the 'twin deficits' in developing economies. It finds that a one percent of GDP unanticipated increase in the government budget balance improves, on average, the current account balance by 0.8 percentage point of GDP. This effect is substantially larger than that obtained using standard measures of fiscal impulse, such as the cyclically-adjusted budget balance. The results point to heterogeneity across countries and over time. The effect tends to be larger: (i) during recessions; in countries (ii) that are more open to trade; (iii) that have less flexible exchange rate regimes; and (iv) with lower initial public debt-to-GDP ratios.